Purification, Modeling, and Analysis of Botulinum Neurotoxin Subtype A5 (BoNT/A5) from Clostridium botulinum Strain A661222 - Jacobson, Mark J. (American Society for Microbiology, 2011)

(untitled)
A Clostridium botulinum type A strain (A661222) in our culture collection was found to produce the botulinum neurotoxin subtype A5 (BoNT/A5). Its neurotoxin gene was sequenced to determine its degree of similarity to available sequences of BoNT/A5 and the well-studied BoNT/A1. Thirty-six amino acid differences were observed between BoNT/A5 and BoNT/A1, with the predominant number being located in the heavy chain. The amino acid chain of the BoNT/A from the A661222 strain was superimposed over the crystal structure of the known structure of BoNT/A1 to assess the potential significance of these differences—specifically how they would affect antibody neutralization. The BoNT/A5 neurotoxin was purified to homogeneity and evaluated for certain properties, including specific toxicity and antibody neutralization. This study reports the first purification of BoNTA5 and describes distinct differences in properties between BoNT/A5 and BoNT/A1.